(untitled) (Journal of the College of Basic Education, 2022)
The researcher used the experimental approach, adopting the experimental design with two equal groups, and the research sample consisted of (20) students distributed equally between two groups, an experimental group consisting of (10) students and a control group consisting of (10) slow learners hyperactive students diagnosed by the hyperactivity scale. Prepared by the researcher, the number of items of the hyperactivity scale in its final form consisted of (48) items, which were defined in four areas: motor, which includes (14) items, distraction, which includes (12) items, and emotional, which includes (11) items.